Accuracy and acceptability of eHealth data collection for an early intensive behavioral intervention program. (13th November 2021) - Pankewich, Amy; Martin, Toby L.; Walters, Kerri L.; Dubé, Charmayne
Abstract: Early intensive behavioral intervention (EIBI) is a treatment designed to increase adaptive behavior and decrease maladaptive behaviors for children with autism spectrum disorder (ASD). EIBI service providers typically collect data using pen‐and‐paper. Participants were four service providers employed at a large community‐based EIBI program. Differences in accuracy between collecting discrete‐trial‐teaching (DTT) data and challenging behavior data using pen‐and‐paper and an eHealth electronic data collection (EDC) application were assessed. The social validity of both methods of data collection was also examined. Pen‐and‐paper and EDC were equally accurate, but participants preferred using pen‐and‐paper. Our accuracy findings agreed with previous comparisons of EDC and pen‐and‐paper. Both methods of data collection are viable for an EIBI program; however, social validity considerations will determine the ease of EIBI programs transitioning to using an eHealth tool for data collection.